Evidence-Based Clinical Practice Guideline: Reconstruction after Skin Cancer Resection. Issue 7 (July 2021) - Chen, Andrew; Albertini, John G.; Bordeaux, Jeremy S.; Chen, Michael W.; Cook, Jonathan L.; Davidson, Caryn; Donnelly, Katelyn C.; Galaria, Irfan I.; Hannan, Catherine M.; Kantor, Jonathan; Kapp, Daniel L.; Lawrence, Naomi; et al.
Abstract : Summary: A multi-disciplinary work group involving stakeholders from various backgrounds and societies was convened to develop guidelines for the management of reconstruction after skin cancer resection. The goal was to identify areas of common ground and provide evidence-based recommendations to improve patient care. Given the heterogeneity of reconstructive techniques and clinical scenarios, investigation centered around common elements in the process. In some cases, a distinction was made between treatment options in the office-based setting as opposed to those in the facility setting. A systematic literature review was performed, and an established appraisal process was used to rate the quality of relevant scientific research (Grading of Recommendations Assessment, Development, and Evaluation methodology). Final recommendations are related to concepts concerning the timing of reconstruction, management of anticoagulation, use of antibiotics, methods of pain control, and follow-up assessment. At times, there was insufficient evidence to make high-level recommendations. The literature analysis highlights the need for additional methodologically robust studies in this area, to help guide clinical practice.